The costs and effectiveness of chemical defenses in herbivorous insects: a meta-analysis - Zvereva EL; Kozlov MV (WILEY-BLACKWELL, 2022)
The evolution of defensive traits and strategies depends on the intensity of selection imposed by natural enemies and on the fitness costs of defenses against these enemies. We tested several hypotheses about the evolution of chemical defenses in plant-feeding insects using a meta-analysis. We analyzed the effectiveness (in terms of prey survival; 159 publications) and costs (in terms of reduction in performance due to defense production; 33 publications) of chemical defenses in various prey-predator systems (140 herbivore species and 124 enemy species). The chemical defenses of insect herbivores, on average, were effective against generalist predators, were not effective against specialist predators and generalist parasitoids, and increased the risk of parasitism by specialist parasitoids. The defenses were more effective against vertebrate than against invertebrate predators and most effective against birds. Defensive compounds synthesized de novo and derived from the herbivore's food plants did not differ in the magnitude of their effects. Externalization of chemical defenses enhanced their effects on naive vertebrate predators but simultaneously increased the risk of parasitism. The defenses of specialist herbivores were more effective than those of generalists, mostly due to species that sequestered plant allelochemicals for their own defenses. Advertising of chemical defenses by warning display enhanced their effectiveness only against vertebrate predators. Aposematic colors and patterns were more effective warning signals than other types of conspicuous coloration against both experienced and naive vertebrate predators, suggesting that certain colors and/or patterns were more important than conspicuousness for both learning and innate avoidance. The meta-analysis did not reveal physiological costs of the production of chemical defenses across 22 herbivore species, although the results varied strongly with the method used to measure these costs. We conclude that the cost-benefit trade-offs driving the evolution of chemical defenses in herbivorous insects are affected by ecological costs (i.e., increased susceptibility to parasitoids) more than by costs in terms of resources. Still, a favorable cost-benefit ratio, i.e., great effects for a small expenditure, may partly explain the prevalence of chemical anti-predator defenses in insects.